EXPLORING DEIXIS IN BBC NEWS: ANALYSIS OF PRAGMATICS - Najmi Naila; Zea Jelika Dewanda; Tatu Siti Rohbiah (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study investigates the use of deixis in a BBC News article titled “Trump blames Zelensky for starting war after massive Russian attack” to explore how language constructs narratives in political conflict reporting. Employing a qualitative descriptive approach grounded in pragmatic analysis, the research identifies and categorizes five types of deixis: person, place, time, discourse, and social deixis. The analysis reveals that person deixis is the most frequently used, emphasizing the roles and responsibilities of political actors, followed by place and time deixis that structure the spatial and chronological context of the news. Discourse and social deixis, though less frequent, contribute to textual cohesion and the representation of institutional roles. The study concludes that deixis functions not only as a linguistic reference but also as a strategic tool for framing meaning, positioning political figures, and shaping public perception. These findings imply that journalists and readers alike should be aware of the pragmatic power of deixis in news discourse, encouraging critical media literacy and reflective reporting, especially in the context of international political conflicts.